Cyclophilin D (PPIF) and MPTP in hepatic ischemia-reperfusion injury: insights into mechanisms - Liu, Jingxin; Wu, Chengyu; Lin, Ziyun; Ma, Maomao; Ma, Wei; Yu, Xuefeng; Wang, Kai; Zeng, Bin (Frontiers in Immunology, 2025)
Hepatic ischemia-reperfusion injury (HIRI) is a major complication in liver transplantation, hepatic surgeries, and shock-induced acute liver failure. This injury is characterized by mitochondrial dysfunction, oxidative stress, and calcium overload, with the mitochondrial permeability transition pore (mPTP) playing a pivotal role in mediating hepatocyte death. Cyclophilin D (CypD), a key regulator of mPTP opening, has long been associated with the exacerbation of HIRI. However, recent research has uncovered a protective aspect of CypD, revealing that it can regulate intermittent or “flickering” mPTP openings to control calcium overload, preserve mitochondrial integrity, and mitigate damage during ischemic stress. This review highlights the dual role of CypD in regulating mitochondrial damage through mPTP dynamics and its complex interplay with autophagy, specifically mitophagy, in liver injury. We also explore the emerging pharmacological and genetic approaches targeting PPIF, offering potential avenues for mitigating liver injury in clinical settings. This review integrates recent findings on PPIF’s role in mPTP regulation, inflammation, autophagy, and mitophagy, proposing a nuanced view of its therapeutic potential in managing hepatic ischemia-reperfusion injury.